Development of Vertebrate Material Instruments to Improve Scientific Literacy - Yuliastrin, Adisti; Arsad, Nurazidawati Mohamad; Wulandari, Eva; Yusra, Nelly; Vebrianto, Rian (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2025)
In theory, educational practices throughout each school day should mitigate the impact of a 21st century pandemic. One of the most important things that needs to be instilled from the start of education is scientific literacy. In this study, an instrument to measure junior high school students' biological literacy was developed and validated. Development. This instrument reproduces the ADDIE model. This instrument is based on the 2013 Biology Science curriculum for class VII and consists of eight literary elements related to biology. Of the 20 topics discussed, there are 5 topics with a nominal dimension, 7 topics with a functional dimension, 4 topics with a structural dimension, and 4 topics with a multidimensional biological literature dimension. Logistic validity assessment was carried out on each content, construction and language of the three validators, then analyzed using the Aiken formula.